Study of hydrolysis conditions of Salmon waste to collect antioxidant peptides - Kieu Anh, Tran; Ha Trung, Nguyen; Khanh Hoang Viet, Nguyen; Thi Hong Loan, Nguyen; Kien Cuong, Pham (VNU Journal of Science: Natural Sciences and Technology, 2017)
Bioactive peptides are considered short chains of 2-20 amino acids, with molecular weights of less than 10.000 Da. They not only have nutritional value but also have positive impacts on body functions and promote health as activities antioxidant, anti-microbial, antithrombotic, immunostimulatory. Many bioactive peptides have been isolated from difference foods: animal (fish, milk, snake venom...), plant (soybean, mushroom...). In this study, we selected hydrolysis conditions of Salmon waste ( Salmo salar) to collect antioxidant peptides.The results show that the appropriate hydrolysis conditions were: Trypsin 2%, pH 8,5, temperature 40''C in 4 hours then Alcalase 2%, pH 8,0, temperature 55 o C in 4 hours, after that they were obtained by ultrafiltration of protein hydrolysate through molecular weight cut-off membranes of 30, 10kDa. The hydrolysis protein solution contains 29,48 mg/ml acid amin and DPPH radical scavenging capacity is 70,34%.